Saving and learning: Theory and evidence from saving for child's college - Junyi Zhu (Deutsche Bundesbank, 2012)
This paper analyzes the main uncertainty of college saving - the child's ability - in the context of the saving with learning model. The first section develops a dynamic model combining asset accumulation and learning to explain the parents' forward-looking saving behavior when they are confronted with the real option of college choice due to uncertainty of their child's ability. The model infers that, with enough time spent learning, information can improve parents' welfare. This can be accomplished by improving the allocation of the consumption to accommodate the burden of college cost given both asset status and the child's true ability. Next, I test the implications of the model from the Panel Study of Income Dynamics/Child Development Supplement & Transition into Adulthood (PSID/CDS & TA) (1997-2005) in the second section. This empirical study investigates college saving behavior when learning is present. Data suggest pessimistic and/or rich parents might reduce the level of college saving, which confirms the interaction of wealth and learning effects predicted by this model. The result also supports the state dependence of parents' college expectations and diminishing persistence over time due to learning. Finally, a number of policy improvements on ESA (Education Saving Account) are proposed to encourage parents to learn about their childs ability.
Keywords: D83; D91; C23; I22; 330; education saving; search; learning; intertemporal consumption; real option; dynamic panel